Studies on the Effect of Alternate Growing Systems and Irrigation Schedules for Soilless Culture of Salad Cucumber - SABEENA SHAHUL; Dr. Rema K. P (Guide) (KCAET Thavanur Department of Irrigation and Drainage Engineering)
ABSTRACT Field study on the effect of alternate growing systems and irrigation schedules for soilless culture of salad cucumber under drip irrigation was conducted inside the naturally ventilated polyhouse in the research plot of Precision Farming Development Centre, in the Instructional Farm of KCAET, Tavanur, during November 2013 to March 2014. In this study coirpith was the media used. The crop water requirement of salad cucumber was determined using CROPWAT model. The data on micro climate inside the polyhouse were periodically recorded on daily basis. The physico chemical and engineering properties of coirpith were studied. The experiment was laid out in a two factor completely randomized block design. The plot was divided into three rectangular sections with three treatments each replicated thrice. The treatments were F1T1 (Black poly bag with daily irrigation), F1T2 (Black poly bag with alternate day irrigation), F1T3 (Black poly bag with irrigation once in 3 days), F2T1 (Lay flat grow bags with daily irrigation), F2T2 (Lay flat grow bags with alternate day irrigation), and F2T3 (Lay flat grow bags with irrigation once in 3 days). Fertigation in coir pith include both macro and micro nutrients applied as water soluble fertilizers from two tanks (tank A and tank B) through fertigation system with venturi. Data about vegetative parameters for each treatment were observed during different stages of crop growth. The results on the effect of alternate growing systems used, irrigation frequency and their combined effect on crop growth and yield parameters were statistically analyzed. Analyzing the effect of alternate growing systems, it was found that vertical type growbag filled with ABSTRACT Field study on the effect of alternate growing systems and irrigation schedules for soilless culture of salad cucumber under drip irrigation was conducted inside the naturally ventilated polyhouse in the research plot of Precision Farming Development Centre, in the Instructional Farm of KCAET, Tavanur, during November 2013 to March 2014. In this study coirpith was the media used. The crop water requirement of salad cucumber was determined using CROPWAT model. The data on micro climate inside the polyhouse were periodically recorded on daily basis. The physico chemical and engineering properties of coirpith were studied. The experiment was laid out in a two factor completely randomized block design. The plot was divided into three rectangular sections with three treatments each replicated thrice. The treatments were F1T1 (Black poly bag with daily irrigation), F1T2 (Black poly bag with alternate day irrigation), F1T3 (Black poly bag with irrigation once in 3 days), F2T1 (Lay flat grow bags with daily irrigation), F2T2 (Lay flat grow bags with alternate day irrigation), and F2T3 (Lay flat grow bags with irrigation once in 3 days). Fertigation in coir pith include both macro and micro nutrients applied as water soluble fertilizers from two tanks (tank A and tank B) through fertigation system with venturi. Data about vegetative parameters for each treatment were observed during different stages of crop growth. The results on the effect of alternate growing systems used, irrigation frequency and their combined effect on crop growth and yield parameters were statistically analyzed. Analyzing the effect of alternate growing systems, it was found that vertical type growbag filled with
Keywords: Irrigation Schedules/ Soilless Culture/ Salad Cucumber/ Drip Irrigation